Case Report: Multi-Orifices Vertebral Arteriovenous Fistula With Severe Scoliosis in Neurofibromatosis Type 1: Might Be a Congenital Disease With Mesodermal Dysplasia - Wang, Yingjin; Yuan, Changwei; Shen, Shengli; Zhang, Yang; Zhang, Jiayong; Duan, Hongzhou (Frontiers in Neurology, 2021)
Background: Vertebral arteriovenous fistula (AVF) associated with neurofibromatosis type 1 (NF-1) is a rare condition in the previous reports. However, whether vertebral AVF in NF-1 is congenital or NF-1 disease progression hasn’t been clarified. Case Description: We reported a 48-year-old male case of vertebral AVF simultaneously combined with thoracic scoliosis and NF-1. Preoperative CT angiography showed the AVF with multiple orifices located on the vessel wall of the vertebral artery, which was proved during the procedure of endovascular treatment. By occluding the parent vertebral artery, the AVF was finally cured. Further whole-exome sequencing identified a novel germline heterozygous point nonsense mutation, c.G397T(p.E133X), in the NF1(NM_000267) gene exon4. Conclusions: From this patient, we speculate that vertebral AVF associated with NF-1 might be a congenital disease as a manifestation of mesodermal dysplasia.